Educational Management Analysis Of The Quality Of Primary School Education In Sidoarjo City : Analisis Manajemen Pendidikan Terhadap Mutu Pendidikan Sekolah Dasar Di Perkotaan Sidoarjo - Asmoro , Cindy Cinthiya Deramerisca; Sari, Della Barokah; Aulia, Jihan Ilmia; Wardhana, Mahardika Darmawan Kusum (Universitas Muhammadiyah Sidoarjo, 2024)
This research article aims to guarantee high quality and fair education. System Theory, this study aims to identify effective education management practices in urban primary schools Sidoarjo.This research is carried out using data compiled and analyzed using a qualitative research model Case Studies. The results show that education management has a positive impact on high-quality education in city schools.The subject of this study is the management of the Basic School of Muhammadiyah 1 Sidoarjo. The results of this research show that internet facilities have a positive effect on quality education, their absence undermines the quality of education in city schools. In addition, it is suggested that the Ministry of Education should arrange professional training for the head of school and teachers to improve their monitoring and supervision strategies.